2017
DOI: 10.1139/cjp-2017-0067
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiosurgery delivery verification using tetrazolium salt-based gel as a dosimeter

Abstract: The recently made available ClearView® tetrazolium salt-based gel dosimeter, encapsulated in a vial, was tested to determine feasibility in use as an end-to-end dosimeter for stereotactic radiosurgery commissioning and quality assurance. A fabricated adaptor enabled direct attachment of the gel vial lid to a rod extension. The rod was inserted into a water-filled head phantom at the open neck location and locked into position. Once quality assurance testing of the linear accelerator was completed, a stereotact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The insoluble formazan dye is spatially stabilized by the gel matrix, which can consist of either gelatine or gellan gum. Practical experience with the use of a commercial ClearView™ dosimeter inserted in a head phantom for the validation of a stereotactic radiosurgery treatment was reported [ 170 ]. The use of a physical gel matrix Pluronic F-127 was suggested as an alternative to gelatine or gellan gum.…”
Section: Radiochromic Gel Dosimetersmentioning
confidence: 99%
“…The insoluble formazan dye is spatially stabilized by the gel matrix, which can consist of either gelatine or gellan gum. Practical experience with the use of a commercial ClearView™ dosimeter inserted in a head phantom for the validation of a stereotactic radiosurgery treatment was reported [ 170 ]. The use of a physical gel matrix Pluronic F-127 was suggested as an alternative to gelatine or gellan gum.…”
Section: Radiochromic Gel Dosimetersmentioning
confidence: 99%
“…However, as initially developed, tetrazolium salt gel dosimeters tend to have lower sensitivity compared to other radiochromic 3D dosimeters [ 3 ], as well as an appreciable dose rate effect at dose rates below approximately 600 cGy/min [ 12 ]. Developed in our laboratory, a new gel dosimeter has been commercialized under the name ClearView by Modus Medical Devices Inc. (Modus QA), (London, ON, Canada) and primarily used for geometric registration of small-beam irradiation [ 14 , 15 , 16 ] and end-to-end dosimetric evaluation of single isocenter multi-target treatment and prostate plan validation [ 17 ]. The initial results indicated that the relatively low sensitivity to dose and the dose rate effect of the sensitivity may cause misregistration of the delivered dose plan.…”
Section: Introductionmentioning
confidence: 99%
“…A normoxic N-Vinylpyrrolidone polymer gel dosimeter was employed for error detection in the E2E test for CT-based brachytherapy [ 25 ]. Gossman [ 26 ] employed a tetrazolium salt-based gel dosimeter as an E2E dosimeter for stereotactic radiosurgery. However, the feasibility of MAGAT-f gel dosimeter for E2E QA for both intensity-modulated radiotherapy (IMRT) and volumetric-modulated arc therapy (VMAT) has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%